(untitled) - Takagi, Rin (Tokyo, Japan, 2020)
This modern version of the Gozen honzo unveils the knowledge it contains, covering 60 ingredients and 70 recipes from the text to reproduce the various delicacies. The exceptional pictures radiate the richness of the dishes, and the additional commentary on culture provides deep insight into how people lived on the islands.
Keywords: Nấu ăn, Nhật Bản,Cooking, Japanese; Phong cách Ryukyu,Ryukyu style